A Non-Invasive Hair Test to Determine Vitamin D3 Levels - Iltaf Shah; Mohammad Mansour; Sheikh Jobe; Emadaldeen Salih; Declan Naughton; Syed Salman Ashraf (Molecules, 2021)
Vitamin D deficiency is being recognized as a global issue and has been implicated in many health issues. Hence, there is an increased interest in developing sensitive, reproducible, and non-invasive assays to measure Vitamin D levels. This study aimed to apply a sensitive liquid chromatography-mass spectrometric assay to hair samples to develop and validate a clinical assay to provide a quarterly average level of vitamin D in one test. Hair samples were collected from 70 male university students/young adults and pulverized/sonicated in methanol/water for 2 h to extract Vitamin D metabolites. A sensitive liquid chromatographic-mass spectrometric assay was employed to quantitate vitamin D and metabolites. Of the eight Vitamin D and metabolites screened, only the primary, clinically significant form of vitamin D (25OHD3) was detected and quantified in hair samples in the range of 17–1541 pg/mg. One-third of the hair samples (21 out of 70) had Vitamin D levels below the LLOD of the assay (10 pg/mg). The mean and standard deviation values for hair (25OHD3) were 276.7 ± 329.9, respectively. This pilot study reveals the potential of the vitamin D hair test in clinical assays as a complementary test to a vitamin D blood test, which would provide a quarterly average.